Fluorescence Radiation and Thermal Effect at the Edge of the Disk-Shaped Laser Crystal - Chen, Yongqian; Chen, Si; Huang, Yuzhi; Jia, Xianshi; Chen, Hantian; Wu, Xiwang (International Journal of Optics, 2022)
The fluorescence radiation property at the edge of the thin disk crystal is very important to the design of thin disk lasers. In order to study this effect, in this paper, we established a theoretical model to describe the edge fluorescence radiation process in thin disk lasers. Subsequently, we used a thin disk crystal with indium absorption cladding to quantitatively test the edge fluorescence intensity. The significant difference between measured and simulated data can be described as P (probability value) < 0.1 at the edge when the measured temperature is lower than the melting point of the metal cladding, and P<0.05 at the pump area. Finally, we analyze the influence of the edge fluorescence radiation on the thin disk laser operation, and the results show that the edge thermal effect will reduce the conversion efficiency of the disk laser by 20%. To the best of our knowledge, this is the first quantitative study on the edge radiation intensity of disk lasers. The research can provide theoretical guidance for the designing and packaging process of crystal elements in thin disk lasers.